Bridges for Academic Success: Opening Spaces for Culturally Responsive Practice in an Urban Pre-School (LEARNing Landscapes, 2015)
It has become widely understood that formal early childhood education can be an important factor in school success. Equally significant is the role of culture as a determinant in negotiating school. Thereby, the inclusion of student culture remains an important aspect in conversations on school success. This discourse is capable of promoting learning using the lives of students by building on what they already know, while offering opportunities for academic achievement. This study investigated how professional development workshops on culturally responsive practice for urban pre-school teachers encouraged the examination of current classroom practices and offered a process for transformation.
Keywords: childhood; culture; education; professonal development; practice